Prevalencia de hipoacusia en niños de 1 a 9 años atendidos en el Centro de diagnóstico audiológico del Hospital Isidro Ayora de Loja de los años 2012-2013 - Guaya Iriarte, Adriana Maribel (2015)
A retrospective, descriptive study was conducted with pediatric patients aged 1-9 years with the purpose to know the prevalence of hearing loss in children who do not have risk factors as well as meet the age which often arises, therefore, must disclose the figures of this problem in children for which we applied the test of steady state evoked potentials ( PEAee ) , this is a test that is performed regardless of age they own. It is emphasized that the existence of hearing loss in pediatric patients has a significant prevalence despite the various difficulties faced by professionals who care for this population since many of these patients do not return for a second review; but according to data collection in the Isidro Ayora Hospital there were 152 patients with hearing that correspond to 100%. The auditory evoked potentials test steady state was used in this study and the results indicated that the prevalence of hearing loss in children of 1-9 years was at the age of six years with 17.10%; also it established that the degree of hearing loss was moderate with 46.05%; it was known that the prevalence of hearing loss according to gender is slightly male majority in the corresponding 51.32% concomitantly distinguish otologic pathologies that produce hearing loss in the study population which was the microtia with 35.3% KEYWORDS: Steady-state evoked potentials, hearing loss, microtia, prevalence, age and gender